Extração de metais pesados de efluentes da indústria do petróleo utilizando derivados de óleos vegetais como extratantes - Santana, Dulcinéia de Castro (2008)
The study of a promising alternative for the treatment of produced water from the oil industry envisaging its reuse was the focus of this work. Millions of liters of water are generated per day, containing heavy metals in low concentrations (< 0,15 mg/L for Pb, <0,04 mg/L for Cd, <0,04 mg/L for Ni). The technology applied to extract these metals from aqueous phase was the solvent extraction and the extratants used were vegetable oils originated from coconut oil. They can be used in natural form or as derivatives, known as MAC - Mixture of Carboxílics Acids. The determination of the heavy metal con¬centrations in a complex matrix was made by using the atomic absorption spectrometry technique (AAS). On the bench tests using synthetics aqueous solutions containing metals, vegetable oils showed no power to extract the metals studied. The extractant MAC was selective for the Pb> Cd> Ni, in the concentration of 8% in the same organic phase. In this condition, the lower efficiency of extraction obtained was 92% for the Pb, 69% for the Cd, in the range of pH ranging from 6 to 8. An experimental planning was conducted for continuous tests. The device used was called MDIF Misturador-Decantador à Inversão de Fases and the aqueous phase was produced water from Pólo Indutrial de Guamaré/RN . No correlation between the studied variables (concentration of metal, concentration of extratant and agitation in the mixing chamer) could be obtained, because of possible factors which occurred as: variation in the composition of the studied sample, phenomena of precipitation and complexation of metals in the reservoir of feed, solubility of extratant